Os bioplásticos: impactos ambientais e perspectivas de mercado - Castro, Thais Hessab Moreira de (2019)
In recent years the conventional plastics market has shown significant growth and the prospect is to maintain the trajectory. The bioplastics market is following the same trend and it has points that must be analyzed to identify the pros and cons related to its production. In this work, results of studies that developed Life Cycle Assessments (LCA) were used to investigate the environmental impacts related to the production of bioplastics and to compare them with conventional plastics. Overall, studies have shown better results in terms of greenhouse gas emissions for bioplastics, however, categories such as acidification and eutrophication have shown opposite results. In addition, a SWOT analysis was performed, in which it was possible to identify that the competition with an already structured market and the higher bioplastics production costs are examples of possible barriers to the consolidation of this market. On the other hand, there is an independence in relation to oil, which has been increasing in price in recent years. It was found that there is room for growth in the sector and it was possible to identify the existence of legislation that stimulates the production of bioplastics. Based on the above, companies have some inputs to assist in the investment decision in the sector.